Territoriality vs Proportionality Concerning Archipelagos Representation: Insular Event - Cabanillas Sanz, Miguel (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2022)
Spanish archipelago representation at the different range of polls is determined by a particular contingency named electoral insular event. Such contingency settles and points at the principle of territoriality over proportionality when it comes to setting up electoral systems on the Balearic and Canary Islands. The current study frames to what extent it is usually seen and which nature lies behind such insular event in Spain, from the Spanish Constitution in 1978 to local Acts. It also provides us with certain solutions to increase proportionality without diminishing a proper representation of such areas of the archipelagos land which makes Spanish Islands.
Keywords: Insular Event; Polls; Election System; Autonomous Lands; Archipelago; Proportionality; Territoriality; Unconstitutionality